The Impact of Inflation, Interest Rates, and Exchange Rates on The Property and Real Estate Sector Stock Price Index for The Period 2021–2024 - Geraldo Apta Andhika; Rosmita Rasyid (CV. Publikasi Indonesia, 2026)
The property sector plays a crucial role in Indonesia's economy, yet its stock market performance often exhibits anomalies that cannot be fully explained by conventional macroeconomic theory. This research aims to analyze the effect of inflation, interest rates, and exchange rates on the Property and Real Estate Sector Stock Price Index (IDXPROPERT) at the Indonesia Stock Exchange for the period 2021–2024. Monthly time series data of 48 observations were analyzed using multiple linear regression after passing classical assumption tests, with data transformation through the first difference method to address autocorrelation issues. The partial test results show that inflation (t = −0.8557, p = 0.3969) and interest rates (t = −0.1946, p = 0.8466) have no significant effect on IDXPROPERT, while exchange rates have a negative and significant effect (t = −2.6222, p = 0.0120). Simultaneously, all three macroeconomic variables significantly affect IDXPROPERT (F = 2.9940, p = 0.0411), with an adjusted R² of 11.51%. In conclusion, among the three variables examined, only the exchange rate consistently serves as a significant predictor of IDXPROPERT performance, reflecting the sensitivity of the property sector to rupiah depreciation through increased import costs and foreign debt burdens. The findings suggest that investors should closely monitor rupiah exchange rate movements in property sector investment decisions. Companies are advised to strengthen exchange rate risk management through hedging instruments.